Preparation method of iron-silicon-based composite soft magnetic powder core

By using air atmosphere heat treatment and nano-oxide insulation coating technology during the preparation process of ferrosilicon powder core, the problem of insufficient loss performance of ferrosilicon powder core under high frequency conditions is solved, and its loss and DC bias are significantly improved. performance.

CN119419058APending Publication Date: 2025-02-11YANGZHOU LEADING INNOVATION MATERIALS TECH CO LTD

Patent Information

Application Number
CN202411819051.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The existing ferrosilicon powder core has high loss performance under high frequency conditions, which limits its promotion and application in high frequency devices, and the improvement effect of single coating technology is not obvious.

Method used

The mixed powder is heat treated with an air atmosphere to achieve uniform oxidation and insulation pretreatment on the powder surface, and nano-oxides are selected as the insulating coating to improve the thermal stability of the insulating layer.

Benefits of technology

The loss performance and DC bias performance of the ferrosilicon-based composite soft magnetic powder core are significantly improved. The DC bias performance of the powder core under 100Oe condition is higher than 76%, and the volume loss Pcv under 50kHz and 100mT conditions is lower than 500mW/cm3.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005182638990000041
    Figure BDA0005182638990000041
Patent Text Reader

Abstract

The invention discloses a preparation method of an iron-silicon-based composite soft magnetic powder core, which comprises the following steps: compounding and uniformly mixing iron-silicon-titanium powder and iron-silicon powder, and carrying out heat treatment in an air atmosphere; and then performing insulation coating on the surface of the magnetic powder by using a polyvinyl alcohol aqueous solution and a nano oxide, and performing compression molding and heat treatment to prepare the iron-silicon-based composite soft magnetic powder core. Compared with a conventional iron-silicon powder core, the iron-silicon-based composite soft magnetic powder core prepared through the method has the advantages that the direct-current bias performance under the condition of 100 Oe is higher than 76%, the volume loss Pcv under the conditions of 50 kHz and 100 mT is lower than 500 mW / cm < 3 >, and the loss performance is obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of soft magnetic materials, and in particular relates to a method for preparing an iron-silicon-based composite soft magnetic powder core. Background Art

[0002] The alloy composition of FeSi powder core is generally 6.5wt% Si and the rest is Fe. The saturation magnetic induction intensity Bs is as high as 1.6T and the effective magnetic permeability is 26-90. Compared with Sendust Aluminum powder core, the most significant feature of FeSi powder core is its higher DC bias performance. At present, the DC bias performance of 60μ FeSi powder core under 100Oe can reach more than 70%, which can be used for the core of power electronic devices in the field of high current and high power.

[0003] Patent CN107610871A discloses a method for preparing low-loss iron-silicon metal soft magnetic powder core for high-power reactors. Phosphoric acid and SiO2 powder are used to insulate and coat iron-silicon powder particles to prepare an iron-silicon soft magnetic powder core with an effective magnetic permeability of 60. The loss of the iron-silicon soft magnetic powder core prepared by the method is less than 600mW / cm at 50kHz and 100mT. 3 , the minimum is 550.87mW / cm 3 In patent CN117038305A, phosphoric acid and hydrogen peroxide were used to insulate and passivate the surface of metal soft magnetic powder, and then silicone high-temperature resin was added to the treated powder to prepare an iron silicon soft magnetic powder core with a magnetic permeability of 60. In the embodiment, the iron silicon powder core prepared by the scheme optimization and the addition of hydrogen peroxide coating scheme has a loss of 613.65mW / cm under 50kHz and 100mT conditions. 3 . Patent CN117747280A discloses a method for preparing an iron-silicon soft magnetic composite material for high frequency. In the scheme, the FeSi raw material powder is first placed on the sand core of the fluidized bed furnace tube, and an Ar-O2 mixed gas is passed through it at 400℃~800℃ for 20~60 minutes to obtain surface-insulated magnetic powder; then the magnetic powder is placed in a double-cone rotary vacuum dryer and coated with a strength enhancer; then a multi-component adhesive transparent solution is formed into a spray and evenly coated on the surface of the magnetic powder to obtain magnetic powder coated with the adhesive; after warm mold pressing, an iron-silicon soft magnetic composite material for high frequency is obtained. The prepared iron-silicon soft magnetic composite material with a magnetic permeability of 64 has a magnetic loss of 10762mw / cm under the conditions of 100mT and 800kHz. 3 .

[0004] With its high Bs and high DC bias performance, FeSi powder core is widely used in high-power photovoltaic inverters, new energy vehicles and their high-power charging piles. However, compared with powder cores such as Sendust and Aluminum, the loss value of FeSi powder core is relatively high, which limits its promotion and application in high-frequency devices. It can be analyzed from existing patents that the loss performance of FeSi powder core can be improved by improving the single coating technology, and the powder core loss level is 600mW / cm 3 For some high-frequency application scenarios, the preparation technology of iron silicon powder core is required, especially the modification of the surface of powder particles requires complicated and customized processing. The process technology is difficult, and the improvement of loss performance under high-frequency conditions is also limited. Summary of the invention

[0005] Aiming at the performance improvement demand of metal soft magnetic powder core, the present invention provides a method for preparing an iron-silicon-based composite soft magnetic powder core. The present invention uses air atmosphere to heat treat the mixed powder to achieve uniform oxidation insulation pretreatment of the powder surface. Furthermore, nano-oxide is selected as the insulating coating to effectively improve the thermal stability of the insulating layer, the subsequent heat treatment temperature of the powder core and the heat resistance temperature of the powder core device.

[0006] The method for preparing the iron-silicon based composite soft magnetic powder core of the present invention comprises the following steps:

[0007] Step 1: Mix the iron silicon titanium and iron silicon soft magnetic powders evenly according to the doping ratio;

[0008] Step 2: heat-treating the mixed powder in an air atmosphere to obtain a pre-treated powder;

[0009] Step 3: Mix the pretreated powder with the polyvinyl alcohol aqueous solution and the nano-oxide, stir evenly, and heat-insulate and dry to obtain the powder to be formed;

[0010] Step 4: Using a press machine, press the magnetic powder to be formed prepared in step 3 into a powder core blank;

[0011] Step 5: Under the protection of inert gas, the powder core blank is kept at 700°C to 780°C to obtain a semi-finished magnetic powder core;

[0012] Step 6: Spray a layer of insulating, high temperature resistant epoxy resin coating onto the surface of the semi-finished magnetic powder core obtained in step 5 to obtain a finished metal soft magnetic powder core.

[0013] In step 1, the original powder particle size of the iron silicon titanium and iron silicon magnetic powder is ≤200 mesh. Among them, the iron silicon titanium component is composed of Si 4.5% to 6.5%, Ti 0.5% to 2.0%, and the rest is Fe; the iron silicon component is composed of Si 5.0% to 6.0%, and the rest is Fe. The mass of the iron silicon titanium powder accounts for 5% to 25% of the total mass of the powder after doping, and the rest is iron silicon powder.

[0014] In step 2, the air atmosphere heat treatment temperature is 250° C. to 400° C., and the heat preservation time is 30 minutes to 60 minutes.

[0015] In step 3, the concentration of the polyvinyl alcohol aqueous solution used is 5% to 15%. Taking the mass of the pretreated magnetic powder as the proportion benchmark, the mass percentage of the added polyvinyl alcohol aqueous solution is 5% to 10%, the mass percentage of the oxide powder is 0.5% to 3.5%, and the mass percentage of water is 8% to 15%; the oxide is one or a mixture of multiple types such as silicon oxide, magnesium oxide, aluminum oxide, etc.

[0016] In step 3, the insulation temperature is 85° C. to 100° C., and the insulation time is 45 minutes to 70 minutes.

[0017] In step 4, the pressing pressure is 1700MPa to 2100MPa.

[0018] In step 5, the insulation time is 120 minutes to 150 minutes.

[0019] In the scheme of the present invention, not only the insulation coating technology is improved, but also low-loss iron silicon titanium powder and iron silicon powder are doped. Iron silicon titanium powder has the excellent characteristics of low loss and corrosion resistance. By adjusting the doping ratio of iron silicon titanium, the loss performance of the iron silicon powder core can be greatly improved, and the DC bias performance of the powder core can also be further improved. The iron silicon titanium and iron silicon mixed powder are heat treated in an air atmosphere, and the surface of the powder is oxidized and passivated once, and the experimental conditions are simple and easy to control. PVP is an amphoteric polymer with good solubility in both polar and non-polar solvents. By adjusting the concentration of the PVP aqueous solution, the viscosity of the solution can be easily adjusted to achieve uniform bonding and modification of the powder surface, and enhance the adhesion with nano oxides. Nano oxides are selected as insulating coatings to avoid crystallization and decomposition of the traditional phosphoric acid passivation insulating layer during the heat treatment process, and improve the thermal stability of the insulating layer. The present invention performs two insulation treatments on the soft magnetic powder particles, which can effectively block the eddy current circuits between the powder particles, greatly improve the loss performance of the iron silicon powder core, and improve the comprehensive magnetoelectric properties of the iron silicon powder core.

[0020] Compared with conventional iron silicon powder core, the iron silicon-based composite soft magnetic powder core prepared by the present invention has a DC bias performance of more than 76% under 100Oe conditions, and a volume loss Pcv of less than 500mW / cm under 50kHz and 100mT conditions. 3 , the loss performance is significantly improved. DETAILED DESCRIPTION

[0021] The present invention is further described below in conjunction with the examples. The described examples and their results are only used to illustrate the present invention, and should not and will not limit the present invention described in detail in the claims.

[0022] Embodiment 1:

[0023] 50.0 g of 200-mesh iron silicon titanium magnetic powder and 950.0 g of 200-mesh iron silicon magnetic powder are selected and mixed evenly; heat treatment is carried out in an air atmosphere at 250° C. for 60 minutes to obtain a pretreated powder; 50.0 g of a 5% PVP aqueous solution, 35.0 g of nano silicon dioxide and 150.0 g of water are added to the pretreated powder, and the mixture is stirred evenly at room temperature; the mixture is then heated to 85° C. and kept warm for 70 minutes to obtain an insulating coated powder; the insulating coated powder is sieved with a 100-mesh sieve to remove coarse particles in the powder, a release agent is added, and the mixture is stirred evenly to obtain a powder to be formed; the powder to be formed is pressed into a powder core blank at a forming pressure of 2100 MPa; the powder core blank is kept warm at 700° C. for 150 minutes in an inert gas atmosphere to obtain a semi-finished magnetic powder core; finally, a layer of insulating coating is sprayed on the surface of the semi-finished magnetic powder to obtain a finished metal soft magnetic powder core.

[0024] Embodiment 2:

[0025] 100.0 g of 200-mesh iron silicon titanium magnetic powder and 900.0 g of 200-mesh iron silicon magnetic powder are selected and mixed evenly; heat treatment is carried out in an air atmosphere at 275° C. for 55 minutes to obtain a pretreated powder; 65.0 g of a 7% PVP aqueous solution, 32.0 g of nano silicon dioxide and 120.0 g of water are added to the pretreated powder, and the mixture is stirred evenly at room temperature; the mixture is then heated to 88° C. and kept warm for 65 minutes to obtain an insulating coated powder; the insulating coated powder is sieved with a 100-mesh sieve to remove coarse particles in the powder, a release agent is added, and the mixture is stirred evenly to obtain a powder to be formed; the powder to be formed is pressed into a powder core blank at a forming pressure of 2000 MPa; the powder core blank is kept warm at 710° C. for 140 minutes in an inert gas atmosphere to obtain a semi-finished magnetic powder core; finally, a layer of insulating coating is sprayed on the surface of the semi-finished magnetic powder to obtain a finished metal soft magnetic powder core.

[0026] Embodiment 3:

[0027] 150.0 g of 200-mesh iron silicon titanium magnetic powder and 850.0 g of 200-mesh iron silicon magnetic powder are selected and mixed evenly; heat treatment is carried out in an air atmosphere at 300° C. for 50 minutes to obtain a pretreated powder; 70.0 g of a 9% PVP aqueous solution, 18.0 g of nano silicon dioxide and 100.0 g of water are added to the pretreated powder, and the mixture is stirred evenly at room temperature; the mixture is then heated to 92° C. and kept warm for 60 minutes to obtain an insulating coated powder; the insulating coated powder is sieved with a 100-mesh sieve to remove coarse particles in the powder, a release agent is added, and the mixture is stirred evenly to obtain a powder to be formed; the powder to be formed is pressed into a powder core blank at a forming pressure of 1900 MPa; the powder core blank is kept warm at 720° C. for 135 minutes in an inert gas atmosphere to obtain a semi-finished magnetic powder core; finally, a layer of insulating coating is sprayed on the surface of the semi-finished magnetic powder to obtain a finished metal soft magnetic powder core.

[0028] Embodiment 4:

[0029] 200.0 g of 200-mesh iron silicon titanium magnetic powder and 800.0 g of 200-mesh iron silicon magnetic powder are selected and mixed evenly; heat treatment is carried out in an air atmosphere at 350° C. for 40 minutes to obtain a pretreated powder; 95.0 g of a PVP aqueous solution with a concentration of 11%, 8.0 g of nano silicon dioxide and 90.0 g of water are added to the pretreated powder, and the mixture is stirred evenly at room temperature; the mixture is then heated to 95° C. and kept warm for 50 minutes to obtain an insulating coated powder; the insulating coated powder is sieved with a 100-mesh sieve to remove coarse particles in the powder, a release agent is added, and the mixture is stirred evenly to obtain a powder to be formed; the powder to be formed is pressed into a powder core blank at a forming pressure of 1800 MPa; the powder core blank is kept warm at 750° C. for 130 minutes in an inert gas atmosphere to obtain a semi-finished magnetic powder core; finally, a layer of insulating coating is sprayed on the surface of the semi-finished magnetic powder to obtain a finished metal soft magnetic powder core.

[0030] Embodiment 5:

[0031] 250.0 g of 200-mesh iron silicon titanium magnetic powder and 750.0 g of 200-mesh iron silicon magnetic powder are selected and mixed evenly; heat treatment is carried out in an air atmosphere at 400° C. for 30 minutes to obtain a pretreated powder; 100.0 g of a 15% PVP aqueous solution, 5.0 g of nano silicon dioxide and 80.0 g of water are added to the pretreated powder, and the mixture is stirred evenly at room temperature; the mixture is then heated to 100° C. and kept warm for 45 minutes to obtain an insulating coated powder; the insulating coated powder is sieved with a 100-mesh sieve to remove coarse particles in the powder, a release agent is added, and the mixture is stirred evenly to obtain a powder to be formed; the powder to be formed is pressed into a powder core blank at a forming pressure of 1700 MPa; the powder core blank is kept warm at 780° C. for 120 minutes in an inert gas atmosphere to obtain a semi-finished magnetic powder core; finally, a layer of insulating coating is sprayed on the surface of the semi-finished magnetic powder to obtain a finished metal soft magnetic powder core.

[0032] The pressed blank in the above embodiment is an annular powder core with an outer diameter of 27.00 mm, an inner diameter of 14.80 mm, and a height of 11.18 mm. The magnetic and electrical properties of the finished powder core are shown in the following table, wherein the diameter of the enameled wire used for the test is Φ1.00 mm, the length is 0.9 m, and the number of winding turns is 25.

[0033]

[0034] According to the size of the powder core magnetic ring, the number of winding turns, and the magnetic permeability, it can be calculated that the inductance value corresponding to the magnetic permeability of 60μ is 46.88μH, and the actual control inductance error is -8% to 8%. It can be seen from the inductance value in the test data that by adjusting the air heat treatment parameters, the amount of insulating coating reagents, and the pressing and heat treatment parameters, an iron-silicon-based composite soft magnetic powder core with a magnetic permeability of 60μ can be adjusted and prepared. In the above embodiment, the doped powder is heat-treated in an air atmosphere, and the surface of the powder is subjected to a primary oxidation insulation to increase the resistivity of the powder surface. Then, the surface of the powder is modified with a PVP aqueous solution to improve the bonding effect between the powder surface and the oxide, achieve secondary insulation on the powder surface, and effectively isolate the eddy current circuit between the particles, thereby greatly improving the loss performance of the powder core.

[0035] Compared with iron silicon powder, iron silicon titanium powder has the excellent characteristics of low loss and corrosion resistance. By adjusting the doping ratio, the DC bias performance and loss performance of the powder core can be effectively improved. From the data test, it can be seen that as the doping ratio of iron silicon titanium powder increases from 5% to 25%, the loss of the prepared iron silicon-based composite soft magnetic powder core increases from 491.85mW / cm 3 Reduced to 401.18mW / cm 3 , which is significantly better than the 620.12mW / cm of the iron silicon powder core 3 Moreover, with the increase of the doping ratio of FeSiTi powder, its DC bias performance under 100Oe conditions can be improved to 77.13%, which is significantly better than the 75.12% of FeSi powder core.

[0036] Therefore, the technical solution of the present invention can significantly improve the performance of traditional iron silicon powder cores, and the comprehensive magnetoelectric properties of iron silicon-based composite soft magnetic powder cores can be conveniently regulated by air heat treatment parameters, doping ratio parameters, pressing molding parameters and heat treatment parameters, which well meets the technical requirements of the current development of power electronic devices for low-loss performance of metal soft magnetic powder cores.

Claims

1. A method for preparing an iron-silicon based composite soft magnetic powder core, characterized in that: Iron silicon titanium powder and iron silicon powder are compounded and uniformly mixed, and heat treated in air atmosphere; then the surface of the magnetic powder is insulated and coated with polyvinyl alcohol aqueous solution and nano-oxide, and an iron silicon-based composite soft magnetic powder core is prepared after pressing and heat treatment.

2. The preparation method according to claim 1, characterized in that The steps include: Step 1: Mix the iron silicon titanium and iron silicon soft magnetic powders evenly according to the doping ratio; Step 2: heat-treating the mixed powder in an air atmosphere to obtain a pre-treated powder; Step 3: Mix the pretreated powder with the polyvinyl alcohol aqueous solution and the nano-oxide, stir evenly, and heat-insulate and dry to obtain the powder to be formed; Step 4: Using a press machine, press the magnetic powder to be formed prepared in step 3 into a powder core blank; Step 5: Under the protection of inert gas, the powder core blank is kept at 700°C to 780°C to obtain a semi-finished magnetic powder core; Step 6: Spray a layer of insulating, high temperature resistant epoxy resin coating onto the surface of the semi-finished magnetic powder core obtained in step 5 to obtain a finished metal soft magnetic powder core.

3. The preparation method according to claim 2, characterized in that: In step 1, the original powder particle size of the iron silicon titanium and iron silicon magnetic powder is ≤200 mesh. Among them, the iron silicon titanium component is composed of Si 4.5% to 6.5%, Ti 0.5% to 2.0%, and the rest is Fe; the iron silicon component is composed of Si 5.0% to 6.0%, and the rest is Fe. The mass of the iron silicon titanium powder accounts for 5% to 25% of the total mass of the powder after doping, and the rest is iron silicon powder. The mass of the iron silicon titanium powder accounts for 5% to 25% of the total mass of the powder after doping, and the rest is iron silicon powder.

4. The preparation method according to claim 2, characterized in that: In step 2, the air atmosphere heat treatment temperature is 250° C. to 400° C., and the heat preservation time is 30 minutes to 60 minutes.

5. The preparation method according to claim 2, characterized in that: In step 3, the concentration of the polyvinyl alcohol aqueous solution used is 5% to 15%. Taking the mass of the pretreated magnetic powder as the proportion basis, the mass percentage of the added polyvinyl alcohol aqueous solution is 5% to 10%, the mass percentage of the oxide powder is 0.5% to 3.5%, and the mass percentage of water is 8% to 15%.

6. The preparation method according to claim 5, characterized in that: The oxide is one of silicon oxide, magnesium oxide and aluminum oxide, or a mixture of more than one of the oxides.

7. The preparation method according to claim 2, characterized in that: In step 3, the insulation temperature is 85° C. to 100° C., and the insulation time is 45 minutes to 70 minutes.

8. The preparation method according to claim 2, characterized in that: In step 4, the pressing pressure is 1700MPa to 2100MPa.

9. The preparation method according to claim 2, characterized in that: In step 5, the insulation time is 120 minutes to 150 minutes.

Citation Information

Patent Citations

  • Method for preparing low-loss iron-silicon metal soft magnetic powder core for high-power electric reactors

    CN107610871A

  • Preparation method of soft magnetic composite material powder

    CN117038305A

  • Preparation method of high-frequency iron-silicon soft magnetic composite material

    CN117747280A

Cited By

  • High direct current bias iron-silicon composite magnetic core for electric reactor, preparation process and electric reactor

    CN120809449A

  • High direct current biasing ferrosilicon composite magnetic core for electric reactor, preparation process and electric reactor

    CN120809449B